Kepemimpinan Yang Efektif Berbasis Kearifan Lokal Sumba TImur di SMA Negeri 1 Pandawai: Effective Leadership Based On Local Wisdom - Lepir, Putiyani Rambu; Ismanto, Bambang (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2024)
This research aims to analyze the relationship between leadership and local wisdom of East Sumba, to describe the characteristics of leadership based on local wisdom of East Sumba, and to analyze the effectiveness of leadership based on local wisdom of East Sumba at SMA Negeri 1 Pandawai. This research is qualitative research with an ethnographic approach. The subjects in this research are community leaders and religious leaders. The second subject in this research was the Principal, Teachers, students and committee of SMA Negeri 1 Pandawai. The data collection techniques used in this research are interview, questionnaire and observation techniques. The data analysis technique used is ethnographic content analysis. The results of the research found by researchers are 1) The relationship between leadership and local wisdom of East Sumba is closely related to traditional beliefs (Marapu), marriage customs (Puru Ngandi), death customs (Taning) where all these customs are closely related to the leadership aspects of direction, influence, communication and guidance. 2) Leadership based on the local wisdom of East Sumba that exists and is commonly used is nicknamed leadership or leadership with the